Whole genome mRNA expression profiling revealed multiple deregulated pathways in stromal vascular fraction from erectile dysfunction patients - Radhakrishnan Vishnubalaji (3563306) (2018)
Background Stem-cell-based therapies have recently been explored in the field of erectile dysfunction (ED). However, the cellular and molecular phenotype of adipose derived stem cells (ADSCs) stromal vascular fraction (SVF) from ED patients remains largely unknown. Herein we compared the global gene expression profile in the SVF from ED patients and healthy individuals and identified altered signaling pathways between the two groups. Methods Samples (2–5 g) of abdominal adipose tissue from ED patients (n = 6) and healthy individual controls (n = 3) undergoing elective cosmetic liposuction were collected. Immediately after removal, SVF was separated using Collagenase type I and type IV protocol. RNA was isolated and microarray experiments were conducted using the Agilent platform. Data were normalized and pathway analyses were performed using GeneSpring software. Results Our data revealed multiple differentially expressed genes between the ED and control group. Hierarchical clustering based on differentially expressed mRNAs revealed clear separation of the two groups. The distribution of the top enriched pathways for the up-regulated genes indicated enrichment in inflammatory response and T-cell receptor signaling, while pathway analysis performed on the down-regulated genes revealed enrichment in mitogen-activated protein kinase, TGF-β, senescence, FAK, adipogenesis, androgen receptor, and EGF–EGFR signaling pathways in SVF from ED patient. Conclusion Our data revealed the existence of multiple altered signaling pathways in the SVF from ED patients, which could potentially play a role in the etiology of this disease. Therefore, therapeutic strategies targeting these pathways might provide novel therapeutic opportunity for ED patients. Other Information Published in: Bioscience Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1042/bsr20181015